Integrating Robotic Fabrication in the Design Process. (May 2014) - Budig, Michael; Lim, Jason; Petrovic, Raffael; Gramazio, Fabio; Kohler, Matthias
Abstract Does the application of robotic technologies in Southeast Asian cities, where the residential high‐rise is pre‐eminent, provide a unique opportunity to introduce bespoke design elements and liberate the high‐rise from serial production and standardisation? Michael Budig, Jason Lim and Raffael Petrovic of the Future Cities Laboratory (FCL) at the Singapore‐ETH Centre for Global Environmental Sustainability (SEC) introduce the research project 'Design of Robotic Fabricated High Rises' (2012‐13) led by Fabio Gramazio and Matthias Kohler, exploring high‐rise typologies and architectural scenarios for future vertical cities.